Experimental study on technological indicators of pile-columns at a construction site - Sivilevičius, Henrikas; Daniūnas, Alfonsas; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Sušinskas, Saulius (Journal of Civil Engineering and Management, 2012)
Decision making is a vital component of success in construction management. All construction businesses recognize the painful necessity of technology choice. Good decisions mean good business. Decisions that are based on knowledge and sound reasoning can lead a company into long-term prosperity. The mandate of a construction management researcher is to use rational, systematic, science-based techniques to inform and improve decisions of all kinds. The paper presents results of an experimental study on technological indicators of pile-columns at a construction site. Based on in-situ investigation of natural soil conditions, regression equations have been determined, which can be very useful when planning similar works at a construction site. Besides, they allow determining duration and energy consumption of construction works.